Double effects of mitigating cyanobacterial blooms using modified clay technology: regulation and optimization of the microbial community structure - Zhu, Jianan; Yu, Zhiming; Cao, Xihua; Jiang, Wenbin; He, Liyan; Zang, Xiaomiao; Song, Xiuxian (Frontiers in Microbiology, 2024)
Harmful algal blooms (HABs) are global hazards under global climate change and eutrophication conditions. Modified clay (MC) method is widely used to control HABs in Asian and American coastal waters. However, little research has been conducted on the underlying mechanisms by which MC controls blooms in freshwater environments. Herein, experiments and bioinformatics analyses were conducted for MC-based control of freshwater blooms in a closed water body with an area of approximately 240 m2 in the Fuchun River, China. Results revealed that the dominant bloom species were Microcystis, and an 87.68–97.01% removal efficiency of whole algal biomass was achieved after 3 h of MC treatment. The weaker zeta potentials of Microcystis species and hydrophilic groups such as O-H and P-O-P in the extracellular polymeric substances (EPS) surrounding Microcystis cells made them easier to be flocculated and removed by MC particles, and the relative abundance of Microcystis decreased to 29.12% and that of Cyanobium increased to 40.97%. Therefore, MC changes the cyanobacterial community structure, which is accompanied by the elimination of Microcystis sp. apical dominance and enhanced competition between Cyanobium and Microcystis in the phytoplankton community, increasing cyanobacterial community diversity. Under MC treatment, residual microorganisms, including cyanobacteria, had a high potential for DNA damage repair and were more likely to survive after being subjected to oxidative stress. In the meanwhile, the abundance of genes involved in genetic information processing, signal transduction, and photosynthesis was decreased indicating that the residual microbiome was week in proliferation and light energy harvesting. Therefore, accompanied with the destruction of Microcystis colonies, MC changes the function of cyanobacteria and phycosphere microbiome, further hindering bloom development. These findings illustrate that MC can regulate and optimize the microbial community structure through which MC controls cyanobacterial blooms in ecosystems.